Variação química do óleo essencial de Hyptis suaveolens (L.) Poit., sob condições de cultivo - Felipe Terra Martins; Marcelo Henrique dos Santos; Marcelo Polo; Luiz Cláudio de Almeida Barbosa (Química Nova, 2006)
This study was performed to establish the correlation between the growth conditions and essential oil composition of Hyptis suaveolens from Alfenas (MG), Brazil. The plants were grown in a greenhouse, four treatments were used and they were harvested at two different periods of time (60 and 135-day-old plants). The essential oil composition was determined by GC-MS analysis. The terpenes spathulenol, globulol, dehydroabietol, a-cadinol and beta-phellandrene were the major constituents found in the essential oil. Oxygenated sesquiterpenes represented the main group of constituents in most of the treatments. The major changes in the essential oil composition were found in 135-day-old plants grown under NPK deficiency. We also identified three groups of volatile components that have not been previously described in H suaveolens.